2001
DOI: 10.1108/07363760110365624
|View full text |Cite
|
Sign up to set email alerts
|

Consumer tradeoffs in on‐line textbook purchasing

Abstract: New forms of retailing present different pricing challenges. The selling of college textbooks over the Internet represents an ideal case study of the different elements that enter into consumer’s price equation. College students were asked to rate the likelihood of purchase of a text given different profiles of sellers and their offerings. Using conjoint analysis, estimates of consumer tradeoffs were calculated. In‐stock status at the college bookstore was the most important variable, followed by buy‐back poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 3 publications
0
14
2
Order By: Relevance
“…Thus participants viewed all image combinations at an equal rate, without becoming overwhelmed by the total possible number of combinations. Results were analyzed using conjoint analysis to estimate consumer tradeoffs when making purchasing decisions between products (Talaga and Tucci, 2001). Conjoint analysis is recognized as being a valuable market research tool in product design (SPSS conjoint 8.0; SPSS), and has been used by researchers to determine which product features consumers feel are important when selecting horticultural goods that will meet a need or want (Kelley et al, 2001(Kelley et al, , 2002.…”
Section: Methodsmentioning
confidence: 99%
“…Thus participants viewed all image combinations at an equal rate, without becoming overwhelmed by the total possible number of combinations. Results were analyzed using conjoint analysis to estimate consumer tradeoffs when making purchasing decisions between products (Talaga and Tucci, 2001). Conjoint analysis is recognized as being a valuable market research tool in product design (SPSS conjoint 8.0; SPSS), and has been used by researchers to determine which product features consumers feel are important when selecting horticultural goods that will meet a need or want (Kelley et al, 2001(Kelley et al, , 2002.…”
Section: Methodsmentioning
confidence: 99%
“…Although the textbook industry may be an oligopoly with four major firms, once the decision is made by a professor to adopt a particular text, the publisher has a monopoly for that course (Iizuka, 2007;Talaga & Tucci, 2001). Faced with a monopolistic situation, students have the option to buy the book new, used, or not at all.…”
Section: The Textbook Price Problemmentioning
confidence: 98%
“…Research related to student behavior and the textbook selection and purchase of textbooks has focused on whether students choose to buy expensive course materials and their perceptions of OERs. Cost is only one factor in student decision-making; whether or not an item is in stock, buy-back prices and return policies are other important considerations (Talaga and Tucci, 2001). Kinskey et al (2018) also demonstrated that students are favorably inclined toward OERs.…”
Section: Introductionmentioning
confidence: 99%